2014
DOI: 10.1001/jama.2014.13573
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fenoldopam on Use of Renal Replacement Therapy Among Patients With Acute Kidney Injury After Cardiac Surgery

Abstract: clinicaltrials.gov Identifier: NCT00621790.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
65
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(69 citation statements)
references
References 33 publications
1
65
1
2
Order By: Relevance
“…Even when looking at a small rise in serum creatinine of 0.3 mg/dl, which would classify as AKI stage 1 according to current Kidney Disease/ Improving Global Outcomes (KDIGO) criteria, acute deterioration in renal function may not be noticeable for >24 h, especially in critically ill patients with fluid accumulation and reduced creatinine generation [4]. These limitations and delays in diagnosis may explain why results from various intervention trials were negative and therapies for AKI are still lacking [5].…”
Section: Predicting Akimentioning
confidence: 99%
“…Even when looking at a small rise in serum creatinine of 0.3 mg/dl, which would classify as AKI stage 1 according to current Kidney Disease/ Improving Global Outcomes (KDIGO) criteria, acute deterioration in renal function may not be noticeable for >24 h, especially in critically ill patients with fluid accumulation and reduced creatinine generation [4]. These limitations and delays in diagnosis may explain why results from various intervention trials were negative and therapies for AKI are still lacking [5].…”
Section: Predicting Akimentioning
confidence: 99%
“…However, a large multi-centre randomised controlled trial of patients undergoing cardiac surgery showed that in patients with AKI fenoldopam did not reduce the need for RRT or 30 day mortality but was associated with increased hypotension (24). Its use is therefore also not currently recommended.…”
Section: Vasodilator Therapymentioning
confidence: 99%
“…Therefore, even the perceived small increase in serum creatinine necessary to reach KDIGO stage 1 criteria for AKI reflects a profound and prolonged decreased in GFR. The negative results of trials aiming to improve the renal outcome in patients with already overt AKI is therefore unsurprising, with most of the patients receiving experimental therapy hours to days following the initial renal insult [8,9]. The need of biomarkers, including functional biomarkers that may rapidly detect changes in GFR and biomarkers of injury that may allow detection of subclinical renal insult, is in this regard obvious.…”
Section: Akimentioning
confidence: 99%